2001
DOI: 10.2337/diacare.24.3.430
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of the Diabetes Control and Complications Trial and Humalog Insulin on Glycohemoglobin Levels and Severe Hypoglycemia in Type 1 Diabetes

Abstract: OBJECTIVE—This study was performed to determine the effects of the Diabetes Control and Complications Trial (DCCT) report in 1993 and the introduction of Lispro (Humalog) insulin in 1996 on glycemic control and on the number of severe hypoglycemic episodes in type 1 diabetic patients of various ages. RESEARCH DESIGN AND METHODS—Diabetes care parameters and HbA1c data from 884 subjects with type 1 diabetes were entered into our database at the time of clinic visits from 1993 through 1998. In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 23 publications
6
59
0
2
Order By: Relevance
“…Although the overall reported rate of hypoglycaemia in the present study was similar to that described recently in an Australian population-based report [33], it is likely to be somewhat less, since the present analysis included episodes of moderate hypoglycaemia that were excluded by Bulsara et al Previous studies from the DCCT [9] and others [37] found that the rate of hypoglycaemia increases with improving metabolic control. It is therefore striking that, in the present study, Maori and Pacific youth had both poor One possible mechanism for this disturbing combination would be a mismatch between insulin administration and food intake or exercise.…”
Section: Discussionsupporting
confidence: 81%
“…Although the overall reported rate of hypoglycaemia in the present study was similar to that described recently in an Australian population-based report [33], it is likely to be somewhat less, since the present analysis included episodes of moderate hypoglycaemia that were excluded by Bulsara et al Previous studies from the DCCT [9] and others [37] found that the rate of hypoglycaemia increases with improving metabolic control. It is therefore striking that, in the present study, Maori and Pacific youth had both poor One possible mechanism for this disturbing combination would be a mismatch between insulin administration and food intake or exercise.…”
Section: Discussionsupporting
confidence: 81%
“…68 From 1993 to 1996, HbA1c continued to decline significantly, but this trend was again associated with a significant increase in the number of severe hypoglycemic events (P<0.001). Starting in the autumn of 1996, a majority (676) of the patients switched to insulin lispro when it first became available.…”
Section: Hypoglycemia Riskmentioning
confidence: 99%
“…This method of HbA 1c analysis has been shown to be accurate in our laboratory. 4 HbA 1c level at the time of study inclusion was used for analyses.…”
Section: Methodsmentioning
confidence: 99%
“…This method of HbA 1c analysis has been shown to be accurate in our laboratory. 4 HbA 1c level at the time of study inclusion was used for analyses.Statistical analyses were performed by using Microsoft (Seattle, WA) Excel 2000 for Windows and analyzed later by using SAS/ STAT, Version 8e (SAS Institute, Inc, Cary, NC) statistical package for Windows. …”
mentioning
confidence: 99%